A bioethical framework to guide the decision-making process in the care of seriously ill patients - Daniel Neves Forte; Fernando Kawai; Cláudio Cohen (BMC Medical Ethics, 2018)
Abstract Background One of the biggest challenges of practicing medicine in the age of informational technology is how to conciliate the overwhelming amount of medical-scientific information with the multiple patients’ values of modern pluralistic societies. To organize and optimize the the Decision-Making Process (DMP) of seriously ill patient care, we present a framework to be used by Healthcare Providers. The objective is to align Bioethics, Evidence-based Practice and Person-centered Care. Main body The framework divides the DMP into four steps, each with a different but complementary focus, goal and ethical principle. Step 1 focuses exclusively on the disease, having accuracy is its ethical principle. It aims at an accurate and probabilistic estimation of prognosis, absolute risk reduction, relative risk reduction and treatments’ burdens. Step 2 focuses on the person, using empathic communication to learn about patient values and what suffering means for the patient. Emphasis is given to learning and active listening, not taking action. Thus, instead beneficence, we trust comprehension and understanding with the suffering of others and respect for others as autonomous moral agents as the ethical principles of Step 2. Step 3 focuses on the healthcare team, having the ethics of situational awareness guiding this step. The goal is, through effective teamwork, to contextualize and link rates and probabilities related to the disease to the learned patient’s values, presenting a summary of which treatments the team considers as acceptable, recommended, potentially inappropriate and futile. Finally, Step 4 focuses on provider-patient relationship, seeking shared Goals of Care (GOC), for the best and worst scenario. Through an ethics of deliberation, it aims for a consensus that could ensure that the patient’s values will be respected as well as a scientifically acceptable medical practice will be provided. In summary: accuracy, comprehension, understanding, situational awareness and deliberation would be the ethical principles guiding each step. Conclusion Hopefully, by highlighting and naming the different perspectives of knowledge needed in clinical practice, this framework will be valuable as a practical and educational tool, guiding modern medical professionals through the many challenges of providing high quality person-centered care that is both ethical and evidence based.